Experiencia profesional adquirida en la empresa Transportes Júpiter SRL - Mananita Flores, Josimar (2022)
The work of professional proficiency presented represents the experience acquired in the company TRANSPORTES JÚPITER S.R.L, in the Department of Safety, Health and Environment. This area's function is to guide management and headquarters in the formulation of procedures and rules, stimulating preventive practices, providing technical knowledge as well as guiding the meetings of the company's safety committee. Likewise, the company, when transporting oil and its derivatives to the different clients it has in the Amazon basin, encounters a series of emergencies that can arise at the docks and along the route of the different vessels, such as: hydrocarbon spills, fire of the boat, collision of boats, man overboard, strandings, river blockades and piracy, natural phenomena that can be heavy rains, electrical storms, strong winds, fog and palisades. Information is also provided on the respective responses for the aforementioned emergencies, as well as the organization of the brigade, indicating their responsibilities as crew members. The graduate in Chemical Engineering finds in this specialty, an enrichment of his knowledge, acquiring new possibilities of professional training but at the same time he has the ability to know and be updated in the current Peruvian regulations on safety and health at work. Due to the above, he presented this report to the students, graduates and teachers of the Faculty of Chemical Engineering, in order to provide a useful tool on safety, health and environmental management.